2010
DOI: 10.1089/acm.2009.0186
|View full text |Cite
|
Sign up to set email alerts
|

A Medicinal Plant Study of the Santal Tribe in Rangpur District, Bangladesh

Abstract: The medicinal plants used by the Santals are worth detailed scientific studies because they are used to treat ailments such as cancer and paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 9 publications
0
49
0
Order By: Relevance
“…Earlier we have published two reports on Santal traditional medicinal usage of plants. The first study on Santal traditional medicine (seven traditional healers were interviewed) was conducted among a community of mixed clans of the Santal people in Rangpur district Rahmatullah et al, 2010), and a second study was conducted among the Murmu clan of the Santals (two traditional healers were interviewed) in Thakurgaon district (Rahmatullah et al, 2009). A comparison of the present survey results with the two previous surveys show that Santal traditional medicinal use of plants vary considerably between different clans of Santals among their scattered communities in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier we have published two reports on Santal traditional medicinal usage of plants. The first study on Santal traditional medicine (seven traditional healers were interviewed) was conducted among a community of mixed clans of the Santal people in Rangpur district Rahmatullah et al, 2010), and a second study was conducted among the Murmu clan of the Santals (two traditional healers were interviewed) in Thakurgaon district (Rahmatullah et al, 2009). A comparison of the present survey results with the two previous surveys show that Santal traditional medicinal use of plants vary considerably between different clans of Santals among their scattered communities in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, treatment of various ailments is done with medicinal plants. We have previously reported Santal medicinal practices of Santals of Rangpur and Thakurgaon districts (Rahmatullah et al, 2009;Rahmatullah et al, 2010). During the course of these studies, it was observed that the use of medicinal plants varied extensively between traditional medicinal practitioners of various clans.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, about 80% population of developing countries still utilizes traditional medicines derived from herbs for their health care (Bargali and Shrivastava, 2002;Shrivastava and Bargali, 2005). As Bangladesh has numerous plants, proper scientific evaluations are required to explore the potentiality of these plants for treating various diseases (Rahmatullah et al, 2010;Banglapedia, 2012;Ashraf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We had been conducting ethnomedicinal surveys among various large and small tribes of Bangladesh for the last few years (Rahmatullah et al, 2009(Rahmatullah et al, , 2010(Rahmatullah et al, , 2011aSeraj et al, 2011). The Mandais are a small tribal community residing in Tangail district of Bangladesh with an estimated population of less than 10,000. region in India for which reason they add the word Cooch to their names.…”
Section: Introductionmentioning
confidence: 99%
“…It would be a loss to science if this knowledge is lost through non-documentation or negligence for many effective drugs in allopathic medicine have been discovered through observation of medicinal practices of indigenous peoples (Gilani and Rahman, 2005). To name only a few, aspirin, atropine, ephedrine, digoxin, morphine, quinine, reserpine and tubocurarine are examples of such drugs.We had been conducting ethnomedicinal surveys among various large and small tribes of Bangladesh for the last few years (Rahmatullah et al, 2009(Rahmatullah et al, , 2010(Rahmatullah et al, , 2011aSeraj et al, 2011). The Mandais are a small tribal community residing in Tangail district of Bangladesh with an estimated population of less than 10,000. region in India for which reason they add the word Cooch to their names.…”
mentioning
confidence: 99%